Feldstein Meets George: Land Rent Taxation and Socially Optimal Allocation in Economies with Environmental Externality - Nguyen Thang Dao; Ottmar Edenhofer (Center for Economic Studies and ifo Institute (CESifo), 2018)
We consider an overlapping generations (OLG) economy with land as a fixed factor of production and an environmental externality on production in which tax revenue from land rent and/or from other schemes such as labor income, capital income, and production taxation can be used for environmental protection through investment in emission mitigation. We show that, for any given target of stationary stock of pollution, the land rent taxation scheme leads to a higher steady state capital accumulation than the other schemes, and hence the steady state consumption of agents when young under this scheme is also higher than under the others. In addition, under an ambitious mitigation target when the efficiency of the mitigation technology is relatively high compared to the dirtiness of production, the land rent taxation also provides a higher steady state consumption when old, resulting in higher social welfare, than the others. In the second part of the paper, we propose a period-by-period balanced budget policy, which includes land rent and capital income taxes with intergenerational transfers, to decentralize the socially optimal allocation during the transitional phase to the social planner's steady state.
Keywords: H23; I31; Q50; 330; overlapping generations economy; land rent; taxation; socially optimal allocation